Three-dimensional analysis of eccentric pounding between two-storey structures using explicit non-smooth dynamics. (15th January 2022) - Ambiel, José Henrique Krahenbuhl; Brun, Michael; Thibon, Alfred; Gravouil, Anthony
Abstract: Pounding research has been gaining momentum in the last decades with large earthquakes hitting cities with insufficiently separated buildings. Even if no major structural damage may be observed in the case of slab–slab pounding, large acceleration pulses may influence the response of equipment and cause disruption in their functionality. In this work, two different models are set up for reproducing shake table tests concerning two-storey adjacent structures, with slab–slab pounding. For the slab representation, the first model uses hexahedral finite elements, while the second one uses shell elements. One of the main objectives of the study is to predict the floor response spectra over a broad frequency range, up to 400Hz. Transient computations of the pounding problem under earthquake excitation are carried out using the explicit CD-Lagrange approach. Rayleigh damping is employed to filter out the spurious high frequency oscillations. The comparison between numerical and experimental results in terms of displacements and floor acceleration spectra shows that the numerical models are able to reproduce the eccentric pounding during the shake table tests. No parameter adjustment related to the contact is required underlining the robustness of the approach. Highlights: Three-dimensional eccentric pounding simulation using explicit non-smooth dynamics. CD-Lagrange method for pounding simulation. No need of parameter tuning in contrast to classical contact elements. Extensive validation of the numerical approach with respect to shake table tests. High frequency branch of the RSA dependent on the highest acceleration impulse